Papillary carcinoma arising in struma ovarii versus ovarian metastasis from primary thyroid carcinoma: a case report and review of the literature - Leite, Inês; Cunha, Teresa Margarida; Figueiredo, José Pinto; Félix, Ana (My University, 2013)
We present a case of a postmenopausal woman diagnosed with an ovarian mass containing thyroid follicles and foci of papillary thyroid carcinoma during pathological examination. This patient referred having had a metachronous thyroid malignancy 10 years before. The differential diagnosis between a thyroid malignancy arising from a struma ovarii and a metastatic ovarian tumor originating from thyroid-cancer is challenging. Struma ovarii should be considered when thyroid components are the predominant element or when thyroid malignant tissue is identified within an ovarian lesion. Thyroid carcinoma arising from a struma ovarii is reported to occur in a minority of cases. Of these, papillary carcinoma is the most frequent subtype encountered. Regarding primary thyroid carcinomas, papillary carcinomas have a lower metastatic potential when compared to follicular carcinomas, and most of the metastases occur in the cervical lymph nodes. Ovarian metastases are exceedingly rare and generally associated with widespread disease. However, they must be considered in the presence of previous history of malignant thyroid carcinoma. The authors review the main clinical, imaging and therapeutic aspects of both these entities and present the most likely diagnosis.